2021
DOI: 10.2503/hortj.utd-217
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Water Supply and Sugar and Capsaicinoids Contents in Fruit of Chili Pepper (<i>Capsicum annuum</i> L.)

Abstract: Environmental factors influence the contents of taste components, such as capsaicinoid compounds, in the fruit of chili pepper (Capsicum annuum). The present research was conducted to evaluate the effect of water supply and harvesting date after flowering on sugar and capsaicinoid contents in fruit of the Japanese chili pepper cultivars 'Botankosho', 'Fushimiamanaga', 'Manganji', and 'Sapporo Oonaga Nanban'. The experiment was conducted in a greenhouse from April to October in 2016 and 2017. Three water supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…4). This result was in line with the authors' previous finding that capsaicinoid content in the placental septum increased under a drought stress condition in Japanese chili pepper varieties 'Botankosho' and 'Sapporo' (Rathnayaka et al, 2020). Estrada et al (1999) also reported that chili fruit was more pungent when grown under drought stress conditions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…4). This result was in line with the authors' previous finding that capsaicinoid content in the placental septum increased under a drought stress condition in Japanese chili pepper varieties 'Botankosho' and 'Sapporo' (Rathnayaka et al, 2020). Estrada et al (1999) also reported that chili fruit was more pungent when grown under drought stress conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Two kinds of stress treatment were used: drought stress treatment and excess water supply treatment. For the drought stress treatment, 150 mL of water was applied for each irrigation, and for the excess water supply treatment, 780 mL of water was applied for each irrigation based on pot size, as described by Rathnayaka et al (2020). In the excess water supply treatment, the excess water that overflowed from the pots was retained in a dish placed under the pot to allow absorption through the pot base.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of soluble solids increased progressively in accordance with the stages of maturation, reaching a maximum value in the red-orange and red stages, with a significant difference for the green-orange and green stages (Table 4). Similarly, Rathnayaka et al (2020) also verified an increase in the soluble solids content in pepper cultivars as the fruits matured. Still, these results corroborate those obtained by Tsegay et al (2013) who evaluated the stages of maturation of sweet pepper fruits (Capsicum annuum L.) and found a progressive increase with fruit maturation, which may have occurred due to the dissociation of some structural organic molecules from soluble compounds.…”
Section: /8mentioning
confidence: 58%
“…Furthermore, the pungency levels of the fruits change under environmental conditions such as soil salinity stress, drought stress, temperature, elevation, and light exposure. It was documented that the capsaicin content was raised in the fruits of C. chinense Jacq under drought stress (Rathnayaka, Kondo, et al, 2021; Rathnayaka, Minami, et al, 2021; Ruiz‐Lau et al, 2011). Also, Purnama et al (2022) found that salinity stress caused an increase in capsaicin content in the hot pepper type of Capsicum annuum .…”
Section: Introductionmentioning
confidence: 99%